Risk Factors of Stunting in Kedisan, Gianyar District, Bali, Indonesia - Luh Gede Pradnyawati; Dewa Ayu Putu Ratna Juwita; Nia Reviani (Jurnal Berkala Epidemiologi, 2021)
Background: Stunting is a nutritional status based on measurements of the Length-for-Age or Height-for-Age index of the anthropometric standards assessment of nutritional status of children. The report of the Public Health Center (PHC) of Tegallalang I revealed the largest number of stunting cases in Kedisan Village, with 28 toddlers suffering from stunting based on 2017 data. Purpose: This study aims to investigate the risk factors associated with stunting at Kedisan Village, Tegallalang Sub-district, Gianyar District. Methods: This is an analytic study employing a case-control approach. Sampling was carried out using a total sampling technique; that is, by utilizing all cases of children under five who were declared stunted in the village in question (a total of 28 cases). The case:control ratio used was 1:1; thus, the total sample used in the study was 56 samples from May 2017. Bivariate analysis was conducted using a chi-square test. Results: The majority of respondents were employed (i.e., 67.80% in the case group and 53.50% in the control group); in terms of the most recent level of education, 35.70% of respondents in the case group had a junior high school education, while 46.40% in the control group had a senior high school education. The results of the bivariate analysis found that the risk factor that was most significantly related with the incidence of stunting was complementary foods with breast milk (p = 0.03; OR: 4.63), while other risk factors were not related to the occurrence of stunting. Conclusions: The factor that influenced the occurrence of stunting in Kedisan Village was complementary foods with breast milk.